Kajian Kriminologi terhadap Pelaku Kejahatan Pembunuhan di Kabupaten Pulau Taliabu Maluku Utara (Studi Sosial Taliabu Barat) - Faisal Batjo; Syawal Abdulajid; Nam Rumkel (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This study analyzes the factors causing criminal homicides in West Taliabu Regency from a criminological perspective, as well as criminal behavior and societal reactions to such crimes. The research methodology employed is empirical legal research using a qualitative field approach, collecting primary and secondary data. The findings indicate internal factors including personal, economic, educational, and familial aspects, while external factors encompass environmental and cultural influences. Some causes include alcohol consumption before homicide and land disputes. The societal response to homicides demonstrates concern and fear, creating discomfort within the community. Formal societal responses involve actions taken by state-recognized community institutions.